Contextualization of Perspective Islamic Moderation KH. Ilyas Kalipaing in Educational Institution - Hamidulloh Ibda; Isni Indriyana (Ar-Raniry: International Journal of Islamic Studies, 2019)
This article examines the dynamics of radicalism and terrorism, biography, thoughts, and the concept of moderating Islam perspective KH. Ilyas Kalipaing. The goal will be achieved to give the idea of moderating Islam perspective KH. Ilyas Kalipaing which can be applied by educational institutions. From the results of the discussion, radicalism and terrorism in this country it is very alarming. The humanitarian crime is not in accordance with Islam rahmatal lilalamin. Islam is a religion of love, tolerance and moderation. But the face of Islam was later defiled by the actions of a handful of groups. So the moderation of Islam is urgent because it is very influential for life and the ongoing Islam in this archipelago. In addition to the Qur’an and the Sunnah, Muslims need Ijma’, Qiyas, Urf, Fikih’ and others so that religion is not merely a testament to and doctrine. The Qur’an and Assunah are the main basis, but in the application there must be moderation of Islam that adapts the reality of the times. Many organizations and figures, kiai, or ulema in this Nusantara have a building of great thought in the moderation of Islam. One of them, KH. Ilyas Kalipaing, a local figure from Temanggung, Central Java who taught how Islam became a loving religion through ideal concepts to learning in Islamic education, as well as the implementation of Islamic moderation. This moderation of Islam must be adapted within the scope of society in general and especially educational institutions through integration in the Character Education Strengthening program.